Research Trends on the Implementation of Digital Literacy in Education: A Bibliometric Analysis of the Scopus Database - Dwi Oktarina, Anisa; Syukrul Hamdi; Ariyadi Wijaya; Zafrullah, Zafrullah; Rashid, Salman (Universitas Muhammadiyah Surakarta, 2025)
This study examines publication trends and research developments in the field of digital literacy in education using bibliometric analysis. A total of 389 documents were retrieved from the Scopus database (2005 to mid-2025) using the keyword Digital Literacy and related educational terms. The PRISMA method was applied to ensure data validity and relevance. The analysis shows a significant increase in publications starting in 2013, peaking in 2023. Universitas Negeri Yogyakarta was identified as the most productive institution, while Indonesia led in publication volume (n=54), although its international collaboration rate remained low (12.85%). Authors from the United States and Indonesia contributed most frequently. The journal “Education and Information Technologies” was found to be the most productive. The most cited articles focused on informal learning, digital generations, and non-formal educational settings. Thematic evolution revealed conceptual deepening and the emergence of multidimensional approaches to digital literacy. Eight keyword clusters were identified, with new topics such as “Artificial Intelligence”, “Self-efficacy”, “Augmented Reality”, and “Inclusive Education” highlighting future research directions. These findings indicate that digital literacy in education now spans technical, pedagogical, affective, and social dimensions. However, this study is limited to the Scopus database and only includes data up to mid-2025. Future research is encouraged to explore digital literacy in specific educational settings such as vocational, out-of-school, and hybrid learning. Additional gaps include teacher competence in AI integration, challenges in inclusive digital learning, and the need for locally relevant digital literacy indicators.